Case Report: AL Amyloidosis Severe Restrictive Cardiomyopathy Associated With Multiple Myeloma—Diagnostic Difficulties - Kirichenko, Yulia Y.; Ilgisonis, Irina S.; Nakhodnova, Elena S.; Sokolova, Irina Y.; Bochkarnikova, Olga V.; Kardanova, Sabina A.; Lyapidevskaya, Olga V.; Privalova, Elena V.; Ershov, Vladimir I.; Belenkov, Yurii N. (Frontiers in Cardiovascular Medicine, 2022)
Background. Cardiac AL amyloidosis as a complication of multiple myeloma (MM) is a formidable life-threatening condition. The first-line therapy for both MM and systemic AL amyloidosis is proteasome inhibitors (PIs). Unfortunately, use of PIs may lead to cardiovasculotoxicity development which requires specific cardio-oncology supervision. Case Report. A 57 years old woman was admitted to a university hospital with a clinical manifestation of progressive chronic heart failure. The patient had hypertension and no history of diabetes mellitus, myocardial infarction (MI), stroke, arrhythmias. After a series of laboratory and instrumental examination methods MM complicated by cardiac AL amyloidosis was proved. On specific cardio-oncology examination: NT-proBNP 4274.0pg/ml; ECHO showed systolic dysfunction, motion abnormalities in LV basal and middle segments, typical depositional myocardium pattern ("luminescence"); cardiac MRI revealed restrictive cardiomyopathy, specific hyperenhancement of the ventricles and atria; 24-hour ECG: QS-pattern in leads V1-V3, unstable ventricular tachycardia (VT) paroxysms. Cardio-oncology consultation: baseline cardiovascular risk was very high (≥20%), cardioprotective therapy (iACE/ARBs, beta-blockers (BB), statins) was administered. The patient underwent VCD [bortezomib; cyclophosphamide; dexamethasone] chemotherapy (CMT) program. By the time of publication the patient had received 4 CMT courses with a positive oncohematological and cardiovascular effect. Conclusion. In this clinical case we described a complication of MM, which was rare according to the severity and manifestation with restrictive cardiomyopathy due to secondary cardiac amyloidosis. The case’s features were the difficulties in verifying the underlying disease and its own complication, the complexity of patient management according to modern principles of cardio-oncology.